Rigid Pavement Engineering of Lake-Musi Rawas Intersection Road Based on 2024 Pavement Design Manual - Nopradego, Rendi; Saloma, Saloma; Usman, Arie Putra (Sean Institute, 2025)
Roads are one of the important elements to improve community economic facilities and infrastructure based on resources, as well as support regions in overcoming rural and sub-district isolation in Musi Rawas Utara Regency (Muratara). The Simpang Lake - Musi Rawas Boundary Road Section is one of the main connecting sections for the community to go to the plantation location and is a priority area in the plantation area. Considering that this section is a priority road section, planning is needed on the Simpang Lake – Musi Rawas Boundary road section using the 2024 Pavement Design Manual. The planned age of the Simpang Lake - Musi Rawas Boundary road section is 20 years with a CBR value of 7.85% JSKN plan of 64,295.49 units, the length of the road tested is 4,800 km. The results obtained are the design of concrete design with a low traffic category with a concrete slab thickness of 200 mm, a thin concrete thickness of 100 mm, an aggregate foundation layer with a thickness of 150 mm and has a Tie Bar with a transverse joint distance of 4.00 m.